Activation of the pp60c-src protein kinase is an early event in colonic carcinogenesis. - Cartwright, C A (1990)
Colonic neoplasia provides an opportunity to study tumor progression because most carcinomas arise from adenomas (polyps), which, in turn, arise from normal epithelia. The malignant potential of adenomas varies with size, histology, and degree of dysplasia. Polyps that are less than 2 cm with villous architecture and severe dysplasia are most likely to contain carcinoma. Previous studies demonstrated that the in vitro protein-tyrosine kinase activity of pp60c-src from colon carcinomas is significantly higher than that from adjacent normal mucosa. Here we report that the protein kinase activity of pp60c-src is also elevated in colonic polyps. Activity is highest in malignant polyps and in greater than 2-cm benign polyps that contain villous structure and severe dysplasia. Thus, pp60c-src activation occurs in benign polyps that are at greatest risk for developing cancer. These data suggest that activation of the protooncogene product pp60c-src may be an important event in the genesis of human colon carcinoma.